2014
DOI: 10.1021/ef500900p
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Partitioning of Di-ethylene Glycol Monomethyl Ether (DiEGME) between Fuel and Aqueous Phases at Sub-Ambient Temperatures

Abstract: Improved understanding of the effect of temperature and concentration on the equilibrium partitioning of Fuel System Icing Inhibitor (FSII) additive between fuel and aqueous phases can assist in identifying required dose concentrations for safe aircraft operability. A novel experimental system was designed and used to quantify the equilibrium partitioning of the currently approved FSII, di-ethylene glycol monomethyl ether (DiEGME), under conditions relevant to actual aircraft fuel system operation. This includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
(35 reference statements)
2
5
0
Order By: Relevance
“…The relationship between freezing point depression as a function of concentration is nonlinear, indicating that the freezing point of the solution does not depend solely on the concentration of the solute, indicating some nonbonded intermolecular interactions between water and the additive (i.e., hydrogen bonding). The measured freezing point values as a function of FSII concentration obtained during these studies were in agreement with those previously reported …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The relationship between freezing point depression as a function of concentration is nonlinear, indicating that the freezing point of the solution does not depend solely on the concentration of the solute, indicating some nonbonded intermolecular interactions between water and the additive (i.e., hydrogen bonding). The measured freezing point values as a function of FSII concentration obtained during these studies were in agreement with those previously reported …”
Section: Resultssupporting
confidence: 92%
“…DiEGME significantly reduced the measured freeze point and broadened the temperature range over which the phase transition occurred. The broadening of the temperature range agreement with those previously reported [37].…”
Section: Experimental Determination Of Ice Formation Inhibitionsupporting
confidence: 92%
See 2 more Smart Citations
“…that more closely replicate actual aircraft system operation (temperature of -47 °C) were simulated. However, the study concentrated on the quantification of equilibrium partitioning of fuel system icing inhibitor (FSII) [116]. Furthermore, from work carried out by the AAIB, a fuel temperature of -35 ºC was estimated with water content between 35 and 40 ppm [1].…”
Section: Complexities Associated With Water Inmentioning
confidence: 99%